The importance of regulatory compliance in wildlife captive breeding: Case study from deer captive breeding in Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Subeno, Pudyatmoko S, Imron MA, Widi TSM. 2022. The importance of regulatory compliance in wildlife captive breeding: Case study from deer captive breeding in Indonesia. Biodiversitas 23: 6128-6136. Indonesia has five deer species that the Indonesian government protects. Among these deer, Javan deer (Rusa timorensis) and sambar deer (Rusa unicolor) have received conservation attention through captive breeding. Despite this conservation approach being applied for these two species, a review on captive breeding implementation is still lacking. This research aimed to assess the management of captive breeding of two deer species, which will support the natural population of endangered species in Indonesia. A triangulation method is used to collect secondary data (documents), interviews, and field observations in Parengan of East Java for Javan deer and Dumai of Riau for sambar deer. Then we assessed the management aspect and the ability of captive breeding to contribute to the release program using descriptive qualitative analysis. The Pertamina RU 2 Dumai sambar deer captive breeding has been carried out since 2016. However, during four years of management, the documents required for captive management, assessed by the Nature Resources Conservation Agency (Balai Konservasi Sumber Daya Alam/BKSDA), were not fully available. Consequently, the population increment in captive breeding could not participate in the release program. The Parengan Javan deer captive breeding was built in 2014. Management documents, population and habitat management were carried out intensively. As a result of the assessment by BKSDA East Java, this captive breeding received an excellent value (A). The population development showed an increasing trend. The results of this population development are then taken 10% to be released into the wild. In 2018, 4 captive-breed Javan deer were released in their natural habitat of Tahura R. Soeryo, East Java. The implication is that captive breeding, which is managed through proper management of population, habitat, and infrastructure, can contribute to supporting the addition of wildlife populations in their natural habitats.
Keywords: Assessment, captive breeding, Javan deer, Sambar deer, triangulation method